Out of curiosity I tried to compute the portfolio weights of a maximum certainty equivalent allocation, however, by incorporating (quadratic) transaction costs. However, my result is not as intuitive as I thought =( I would be happy for each and every hint to solve this problem:

Let the parameters of the return distribution be $\Sigma$ and $\mu$. The current allocation vector is $\omega_c$. The risk aversion factor of the investor is defined as $\gamma$. When shifting his wealth to allocation $\alpha$, the investor pays a fee of the form $T = c(\alpha - \omega_c)'(\alpha - \omega_c)$ with some parameter $c$, therefore transaction costs increase quadratically by factor $c$. Therefore, at time point $t+1$ the investor expects the portfolio returns to be $$\mu_\text{PF} = \alpha'\mu - T(\alpha,\omega_c)$$ and the corresponding variance of the portfolio $$\sigma^2_\text{PF} = \alpha'\Sigma\alpha.$$ In one line, the allocation is chosen as the solution to the maximization problem $$\alpha^* = \arg \max _{\sum \alpha = 1} \alpha'\mu - T(\alpha,\omega_c) - \frac{\gamma}{2}\alpha'\Sigma\alpha.$$ Equivalently, we have: $$\alpha^* = \omega_c + \arg \max _{\sum \Delta = 0} (\omega_c+\Delta)'\mu - c\Delta'\Delta - \frac{\gamma}{2}(\omega_c+\Delta)'\Sigma(\omega_c+\Delta).$$ $$ \Delta^* = \arg \max _{\sum \Delta = 0} \underbrace{\omega_c '\mu - \frac{\gamma}{2}\omega_c'\Sigma\omega_c}_{CE(\omega_c)} +\Delta'\mu - c\Delta'\Delta - \frac{\gamma}{2}\Delta'\Sigma\Delta - \gamma \Delta'\Sigma\omega_c.$$ $$ \Delta^* = \arg \max _{\sum \Delta = 0} \Delta'\mu - \Delta'\underbrace{(c I + \frac{\gamma}{2}\Sigma)}_{:=A}\Delta - \gamma \Delta'\Sigma\omega_c.$$

The first-order conditions take the form: $$\mu - 2A\Delta - \gamma \Sigma\omega_c -\lambda\iota= 0$$ $$ \iota ' \Delta = 0$$ It follows that $$A^{-1} (\mu-\gamma \Sigma \omega_c - \lambda \iota) = 2\Delta$$ Evaluating $\iota'\Delta = 0$ with $\Delta$ as above results in $$\lambda = \frac{1}{\iota' A^{-1}\iota}\iota'A^{-1}[\mu - \gamma \Sigma \omega_c]$$ Plug-in gives $$\Delta = A^{-1} (I - \frac{1}{\iota'A^{-1}\iota} \iota' A^{-1}\iota) (\mu-\gamma \Sigma \omega_c ) = 0\iota.$$ In other words, no matter how sub-optimal the current allocation and irrespective of the sice of $c$, there will never be any rebalancing. I do not believe this result but I also do not see the mistake in my computations. Anyone an idea, where did I miss something/ did something wrong?


2 Answers 2


Seems like a small mistake in the last equation. It should read

$\Delta^* = A^{-1} \left[\mu-\gamma \Sigma \omega_c - \frac{1}{\iota'A^{-1}\iota} \iota' A^{-1}(\mu-\gamma \Sigma \omega_c )\iota\right]$,

which is not equivalent to your result.


You would like to solve the following optimisation problem:

\begin{gather} \Delta^* = \arg \max_\Delta \Delta^T\mu - \Delta^T A \Delta - \gamma \Delta^T \Sigma\omega_c\\ \text{subject to:}\quad \Delta^T \mathbf{1} = 0 \end{gather}

Build the Lagrangian $$ \mathcal{L}(\Delta,\lambda) = \Delta^T\mu - \Delta^T A \Delta - \gamma \Delta^T \Sigma\omega_c - \lambda(\Delta^T \mathbf{1}) $$

First order KKT conditions then yield:

$$\partial_\Delta \mathcal{L}(\Delta^*,\lambda^*) = \mu - A\Delta^* - \gamma\Sigma\omega_c - \lambda^*\mathbf{1} = \mathbf{0} \tag{1}$$

along with $\partial_\lambda \mathcal{L}(\Delta^*,\lambda^*)=0$ (which is precisely the constraint equation)

$(1)$ is equivalent to writing $$ \Delta^* = A^{-1}(\mu-\lambda^*\mathbf{1} - \gamma\Sigma\omega_c) \tag{2}$$

Plugging this into the constraint equation then gives: \begin{align} &(\mu-\lambda^*\mathbf{1} - \gamma\Sigma\omega_c)^T(A^{-1})^T \mathbf{1} = 0 \\ &\mu^T (A^{-1})^T \mathbf{1} -\lambda^*\mathbf{1}^T (A^{-1})^T \mathbf{1} -\gamma\omega_c^T\Sigma^T (A^{-1})^T \mathbf{1} = 0 \end{align} Noting that $A := \frac{\gamma}{2}\Sigma + cI$ is symmetric, i.e. $(A^{-1})^T = A^{-1}$ further yields, as you mention: $$ \lambda^* = \frac{1}{\mathbf{1}^T A^{-1} \mathbf{1} } \mathbf{1}^T A^{-1} (\mu -\gamma \Sigma \omega_c ) \tag{3}$$ Plugging $(3)$ into $(2)$ finally gives: $$ \Delta^* = A^{-1}\left( \mu - \gamma\Sigma\omega_c - \frac{1}{\mathbf{1}^T A^{-1} \mathbf{1} } \mathbf{1}^T A^{-1} (\mu -\gamma \Sigma \omega_c ) \mathbf{1} \right) $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.